PERSEPSI PETANI KOPI TERHADAP PROGRAM SERTIFIKASI RAINFOREST ALLIANCE COFFEE (RFA) DI KECAMATAN PULAU PANGGUNG KABUPATEN TANGGAMUS - Erviza Feby Triana; Tubagus Hasanuddin; Indah Nurmayasari (Lampung University, 2019)
This research aims to find out: farmers' perception on Rainforest Alliance (RFA) coffee certification program, Factors related to the perception,income of farmers joining the program, andorrelation between the perception and coffee farming income. This research was conducted in TanjungRejo Village, PulauPanggung Subdistrict, Tanggamus District in August-September 2017. The selection of the location was determined purposively considering that the area has the highest number of farmers who join RFA certification. The respondents were 64 coffee farmers who have RFA Coffee certificate. The method used is a survey method. Data are analyzed descriptively and using rank Spearman correlation. Results indicated that: perception of coffee farmers on RFA certification program is included in the high classification. Factors significantly correlated to coffee farmers' perception on the RFA certification program are farmers’ knowledge and social interaction. Coffee farming income in 2017 was Rp19,908,000.00 per hectare per year, decreased from Rp21,092,375.00 per hectare per year in 2016. The decline is due to bad weather and pest/disease outbreak.Key words: coffee farmers, farm income, perception, RFA